Spectrophotometric Estimation of Rifampicin in Capsules - Mathrusri Annapurna, M.; Nagoji, K.E.V.; Vijay Srinivas, S.; Patro, S. (Asian Journal of Chemistry, 2010)
A simple and reproducible spectrophotometric method have been developed for the estimation of rifampicin in pure and its capsules by using 0.1 M copper nitrate in presence of 1 M potassium nitrate. Beer's law was obeyed in the concentration of 5–100 μg/mL at 410 nm and 568 nm. The colour is stable for more than 24 h.